Carotid atherosclerosis and lectin-like oxidized low density lipoprotein receptor-1 levels in hemodialysis patients - Dagel, Tuncay; Gönenli, Mehmet Gökhan; Kahvecioğlu, Serdar (The European Research Journal, 2022)
Objectives: Atherosclerotic cardiovascular disease risk is increased in hemodialysis patients. Oxidized low density lipoprotein has an important role in atherosclerotic process and it exerts this effect via lectin like oxidized low density lipoprotein-1 (LOX-1). Carotid artery intima-media thickness (CIMT) is accepted as a god indicator of subclinical atherosclerosis. In this study, we aimed to investigate LOX-1 and CIMT levels in hemodialysis patients. Methods: Twenty-eight patients treated with hemodialysis at least 6 months and 19 healthy subjects were enrolled in this study. Serum LOX-1 levels and simultaneously with CIMT were measured in hemodialysis patients and healthy control group. Results: CIMT value was found to be statistically significantly higher in the hemodialysis group compared to control group (0.9 mm in hemodialysis group vs. 0.7 mm in control group, p < 0.001). There was no statistically significant difference between groups in terms of LOX-1 levels. (0.172 ng/ml in hemodialysis group vs. 0.213 ng/ml in healthy control group, p > 0.05). Conclusions: Although cardiovascular risk markers like CIMT, CRP were higher in hemodialysis group as expected, increase in LOX-1 levels was not detected.